Rediscovering compact cities for sustainability - Newman, Peter (Edward Elgar Publishing Limited, 2014)
Density is a key factor in the growth of cities, the happiness of cities, and the wealth of nations. And cities and regions where density is more concentrated near their urban cores – appear to gain the biggest economic advantage.